Measurement of Weight in Clinical Trials: Is One Day Enough?. (27th July 2010) - Maruthur, Nisa M.; Vollmer, William M.; Clark, Jeanne M.; Jerome, Gerald J.; Lien, Lillian F.; Loria, Catherine M.; Appel, Lawrence J.
Abstract : Background . Weight is typically measured on a single day in research studies. This practice assumes negligible day-to-day weight variability, although little evidence exists to support this assumption. We compared the precision of measuring weight on one versus two days among control participants in the Weight Loss Maintenance trial. Methods . Trained staff measured weight on two separate days at baseline, 12 months, and 30 months (2004–2007). We calculated the standard deviation (SD) of mean weight change from baseline to the 12- and 30-month visits using (a) the first and (b) both daily weights from each visit and conducted a variance components analysis (2009). Results . Of the 316 participants with follow-up measurements, mean (SD) age was 55.8 (8.5) years, BMI was 30.8 (4.5) kg/m 2, 64% were women, 36% were black, and 50% were obese. At 12 months, the SD of mean weight change was 5.1 versus 5.0 kg using one versus two days of weight measurements( P = .76 ), while at 30 months the corresponding SDs were 6.3 and 6.3 kg( P = .98 ) . We observed similar findings within subgroups of BMI, sex, and race. Day-to-day variability within individuals accounted for <1% of variability in weight. Conclusions . Measurement of weight on two separate days has no advantage over measurement on a single day in studies with well-standardized weight measurement protocols.